Pendampingan Pengelolaan UKM Sandal Melalui Brand dan Packaging di Desa Nogosari Kabupaten Pasuruan - Wahid, Abdul; Nuriyanto; Dayat, M. (Program Studi Ekonomi Pembangunan, 2024)
Alkopini is a small and medium enterprise engaged in the manufacture of hommade sandals with synthetic leather as the basic material. The purpose of this service is to help expand the market and increase the selling value in the market by introducing the brand more widely to the community in the Pasuruan Regency area. In this service method using SWOT analysis. The results of the service show an increase in the production of the Alkopini praduk from 15 pairs of sandals a day to 20 to 25 pairs of sandals a day. Through this community service, the service team helps expand the Alkopini sandal market by using brands and packaging with the aim of attracting more consumers and using the sandal products produced and increasing the selling value of each product produced.